Bisnis Online: Saving The Future - Mohamad Saiful Muarifin; Riris Dwi Anjani; Masduki Asbari; Adhik Ryan Niko Putratama (Yayasan Aya Sophia Indonesia, 2023)
The purpose of this research is to find out Jeff Budiman's perspective from the TEDxTalks youtube channel entitled